Precalving Nutrition of Beef Females in Florida - Philipe Moriel; Joao Vendramini (EDIS)
This publication was developed for beef cattle producers to modify the supplementation strategy during the precalving period to improve calf performance after birth. Written by Philipe Moriel and Joao Vendramini, and published by the UF/IFAS Department of Animal Sciences, April 2023.